Difficulties encountered by third year high school students in solving verbal problems using linear equations - Mateo, Efren B. (1979)
This study attempted to analyze and interpret the difficulties encountered by third year high school students in solving verbal problems involving linear equations. A diagnostic test was constructed by the researcher. The results of this study showed that the students of Saint Mary's College, High School Department, Nueva Vizcaya were generally poor in solving verbal problems in mathematics.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines -- Bayombong (Nueva Ecija); Linear equations; Problem solving; Mathematical ability -- Testing; Academic achievement -- Philippines -- Bayombong (Nueva Ecija)